Cinco de mayo : a Mexican holiday about unity and pride - Garcia, James (Chanhassen, MN. : Child's World, 2003)
Explores the history, customs, and practices of this holiday that commemorates the victory of the Mexican army over the French on May 5, 1862.
What is Cinco de Mayo? -- Celebrating Cinco de Mayo -- Making your own Cinco de Mayo fiesta -- Who celebrates Cinco de Mayo?
Includes bibliographical references and index.
Accelerated Reader
Keywords: Cinco de Mayo (Mexican holiday).; Mexico -- Social life and customs